Elevated Systemic Levels of Eosinophil, Neutrophil, and Mast Cell Granular Proteins in Strongyloides Stercoralis Infection that Diminish following Treatment - Rajamanickam, Anuradha (Front Immunol, 2018)
Infection with the helminth parasite Strongyloides stercoralis (Ss) is commonly clinically asymptomatic that is often accompanied by peripheral eosinophilia. Granulocytes are activated during helminth infection and can act as immune effector cells. Plasma levels of eosinophil and neutrophil granular proteins convey an indirect measure of granulocyte degranulation and are prominently augmented in numerous helminth-infected patients. In this study, we sought to examine the levels of eosinophil, neutrophil, and mast cell activation-associated granule proteins in asymptomatic Ss infection and to understand their kinetics following anthelmintic therapy. To this end, we measured the plasma levels of eosinophil cationic protein, eosinophil-derived neurotoxin, eosinophil peroxidase, eosinophil major basic protein, neutrophil elastase, myeloperoxidase, neutrophil proteinase-3, mast cell tryptase, leukotriene C4, and mast cell carboxypeptidase-A3 in individuals with asymptomatic Ss infection or without Ss infection [uninfected (UN)]. We also estimated the levels of all of these analytes in infected individuals following definitive treatment of Ss infection. We demonstrated that those infected individuals have significantly enhanced plasma levels of eosinophil cationic protein, eosinophil-derived neurotoxin, eosinophil peroxidase, eosinophil major basic protein, elastase, myeloperoxidase, mast cell tryptase, leukotriene C4, and carboxypeptidase-A3 compared to UN individuals. Following the treatment of Ss infection, each of these granulocyte-associated proteins drops significantly. Our data suggest that eosinophil, neutrophil, and mast cell activation may play a role in the response to Ss infection.